Randomized Controlled Trial: Effectiveness of Ankle Support in Reducing Ankle Sprain Pain in Futsal Players - Ningsih, Cica Tri Mandasari; Septiani , Anissa Eka (Journal of Prosthetics Orthotics and Science Technology, 2024)
Background: Many people worldwide engage in sports as a hobby, for health training, work, fitness, and relaxation. However, physical activity can also lead to injuries, as can workplace accidents, traffic incidents, and mishaps at home. One common injury is an ankle sprain, particularly prevalent among highly active individuals. Several treatments are available for ankle injuries, with conservative early intervention being the preferred approach. The RICE method (Rest, Ice, Compression, and Elevation) is commonly employed initially, which can be supplemented with protection and rehabilitation to form the PRICE regimen. Protection involves immobilization, which aids in pain and swelling reduction. Additionally, medications play a role in alleviating pain and swelling. Following conservative treatment, functional intervention utilizing external support is often employed to enhance ankle joint function and stability. In cases where conservative measures fail to yield satisfactory results, surgical intervention may be necessary to improve joint stability. Aims: This study aims to assess the effectiveness of ankle support in alleviating pain among futsal players who have sustained ankle sprains. Methods: The research adopts an experimental design, specifically a randomized controlled trial (RCT), employing simple randomization to form two groups: the control group and the treatment group. Results: Non-parametric tests utilizing the Mann-Whitney Test yielded a probability value of 0.693 (> 0.05), leading to the rejection of the hypothesis. Conclusion: Consequently, the study's findings indicate no significant difference in pain reduction between futsal players who use ankle support and those who do not follow ankle sprains.